Development of IES (Innovation Entrepreneurship System) Application Mobile for Start-Ups Using Service Science Perspective (Study Case: LPIK ITB) - Utari, Mentari Nur; Novani, Santi (The Asian Journal of Technology Management (AJTM), 2021)
Institute of Innovation and Entrepreneurship Development (LPIK) ITB is established as a hub to commercialize the innovation as well as an entrepreneurship development for ITB academic community. Many organizations including LPIK still deny how Industry 4.0 can influence businesses or struggle to find  the talent or knowledge how to adopt it. LPIK applies change and prepares a future where intelligent machines improve their business goals. One of them is the existence of mobile applications to create value co-creation. This study using service science perspective to portray LPIK ITB. The methodology used is using a mix methodology. First, quantitative survey is conducted to measure the service quality (SERVQUAL) then qualitative study is conducted by exploratory approach using in-depth interviews and FGDs. Using service science approach, we identify the failed points using blueprints method and design thinking to create for product innovation features. The result of this study is proposed four development programs to improve IES LPIK ITB services, i.e, IES Shop along with the UI/UX features of the standalone service system and as a liaison between the Customers, Mentors, Industries, Investors, and Employees at LPIK involved (Proposed Prototype), Design Service Blueprint (Customer Oriented), Integrated People Development Program, and Digital Experience Development Program.